Highlights on Novel Imaging Methods of Pancreatic Cancer - Krishnamoorthy, Saravanan Kokila; Hayim, Morris; Vestal, Tyler; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is the fourth leading cause of cancer deaths. Since the majority of patients present with incurable metastatic disease, novel imaging methods are needed to identify pancreatic cancer and assess response to therapy. Research presented at the 2013 American Society of Oncology (ASCO) Annual Meeting provided insight into potential imaging methods. We discuss Abstracts #4049, #TPS4144, #TPS4146, and #E15069 in this paper. Image: Contrast enhanced MRI of pancreatic adenocarcinoma.